2005
DOI: 10.1063/1.2039078
|View full text |Cite
|
Sign up to set email alerts
|

Ion-induced nucleation in polar one-component fluids

Abstract: We present a Ginzburg-Landau theory of ion-induced nucleation in a gas phase of polar onecomponent fluids, where a liquid droplet grows with an ion at its center. By calculating the density profile around an ion, we show that the solvation free energy is larger in gas than in liquid at the same temperature on the coexistence curve. This difference much reduces the nucleation barrier in a metastable gas.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
17
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(21 citation statements)
references
References 25 publications
(52 reference statements)
4
17
0
Order By: Relevance
“…Specifically, when the free energy as a function of n exhibits both a minimum (at n 0 ) and a maximum (at n * ) the nucleation barrier is usually defined as G 0 = G(n * ) − G(n 0 ) [6,7,9,10,17,18,23,25,26,[44][45][46][47][48]. However, this definition is an approximation that becomes increasingly inaccurate in the low-barrier regime.…”
Section: Comparison Of Barrier Definitionsmentioning
confidence: 99%
“…Specifically, when the free energy as a function of n exhibits both a minimum (at n 0 ) and a maximum (at n * ) the nucleation barrier is usually defined as G 0 = G(n * ) − G(n 0 ) [6,7,9,10,17,18,23,25,26,[44][45][46][47][48]. However, this definition is an approximation that becomes increasingly inaccurate in the low-barrier regime.…”
Section: Comparison Of Barrier Definitionsmentioning
confidence: 99%
“…which was already introduced by Eq. 3, and the Rayleigh radius, R 3 R = (qe) 2 (1/ v − 1/ l ) / 64π 2 0 γ lv , we can rewrite the last equation concisely as [16][17][18]31…”
Section: B Nucleation In Presence Of Charged Species: the Thomson Modelmentioning
confidence: 99%
“…[12][13][14] (2) Few theoretical and computational studies have been reported on the effect of ions on water condensation. [15][16][17][18][19] (3) Vapor-liquid equilibrium is known to be very sensitive to the interaction potential and the many-body nature of the interaction. Recently, it was reported 20 the impact of various intermolecular potentials on the vapor-liquid equilibrium of argon.…”
Section: Introductionmentioning
confidence: 99%
“…This theory has to be quantitatively correct in the sense that it withstands the comparison with MC simulation data and it has to be easily applicable for interpreting corresponding experimental data. We expect that our model calculations can be used to shed light on the role of nonlinear dielectric saturation for solvation effects of ions in dipolar solvents [28,29].…”
Section: Introductionmentioning
confidence: 99%